Design and Analysis of an Underwater White LED Fish-Attracting Lamp and its Light Propagation. (29th March 2013) - Shen, Sheng Chih; Kuo, Cheng Yuan; Fang, Ming-Chung
Light emitting diodes (LED) are a new source for replacing traditional light sources including under water illumination. As traditional underwater light sources operate under a radiative transfer model, the luminous intensity is dispersed evenly at each emission angle, with the scattering factors included in the attenuation coefficient. By contrast, LED light sources are characterized by being highly directional, causing underwater luminous energy to vary with different emission angles. Thus, the traditional theory of underwater optical transfer becomes inapplicable when an underwater LED lighting module is designed. Therefore, to construct an underwater transfer model for LED light sources, this study employed the average cosine of the underwater light field, the method for light scattering probability, the LED luminous intensity distribution curve (LIDC) and axial luminous intensity. Afterwards, an underwater LED fish-attracting lamp was designed. Experimental results showed that, compared with the simulation values, the luminous intensity of the underwater LED lighting module at all emission angles had a percentage error of less than 10%.